2016
DOI: 10.4103/2231-0762.192947
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of palatal rugae pattern in central Indian population

Abstract: Aim:The aim of this study was to analyze the morphological study of palatal rugae pattern in a central Indian population and to determine sex differentiation.Objectives:To investigate the distinctive rugae patterns of the study population and determine the contribution of rugae patterns in gender identification.Material and Methods:The present cross-sectional study was conducted among a Central Indian population with a sample size of 500 participants. The study involved 250 males and 250 females who were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
2
9
0
1
Order By: Relevance
“…12 Pereira et al 11 reported that both forward and backward were common in males, while perpendicular patterns were common in females, while Dwivedi and Nagarajappa reported that backwardly directed rugae were common in males. 24 In agreement with our study's findings, previous studies have demonstrated no significant difference between males and females. 4,5 This finding was contrary to an earlier study that reported a higher number of rugae in males than females.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…12 Pereira et al 11 reported that both forward and backward were common in males, while perpendicular patterns were common in females, while Dwivedi and Nagarajappa reported that backwardly directed rugae were common in males. 24 In agreement with our study's findings, previous studies have demonstrated no significant difference between males and females. 4,5 This finding was contrary to an earlier study that reported a higher number of rugae in males than females.…”
Section: Discussionsupporting
confidence: 93%
“…7 However, the findings of our study do not support the results of previous studies. 23 Studies have reported that males' most common pattern was a wavy pattern 9,24,25 and in females was a curved pattern. 9,14 The wavy pattern followed by a straight pattern was predominantly seen in females, while the curved pattern was seen most commonly in males.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying individuals with visual tests, fingerprints, and DNA is a method developed in the world of forensic identification, but the cost of DNA test isn't low and fingerprint is not always obtained, for example on burnt victim. 6 This study indicates that the type IV palatal rugae direction is dominant in both male and female maxilla, with 94% percentage in boys and 85% in girls.…”
Section: Discussionmentioning
confidence: 66%
“…This study group showed more backward directed rugae compared to forward and perpendicular rugae which is similar to the Bengali population (28). In contrast, forward directed rugae was predominant in Sudanese, Egyptians, Turkish, Gujarati, and Indians (22,27,(29)(30)(31)(32)(33). Generally, the population worldwide would show more forward directed rugae because there is a decrease in backward directed rugae with age.…”
Section: Discussionmentioning
confidence: 99%